Mobile Cities. - Verzosa, Nina; Legacy, Crystal (Palgrave Macmillan, 2020)
The chapter provides a discussion of critical questions surrounding mobile cities. What is a mobile city? How is it formed? Who shapes it and who benefits from it? The chapter starts with a definition of a mobile city, then discusses the three key planning processes that emerged since the mid-twentieth century and how these processes have prevailed or shifted in recent times. The three key planning processes are (1) rational-technical planning, (2) sustainability planning and (3) social justice planning. The chapter explores the role of planners as they redefine the highly contested understanding of public interest while navigating major transportation projects and policies. The chapter concludes by examining what new challenges await planners as the future of urban mobility is shaped by digitally mediated transportation solutions.
Keywords: Mobilität; Mobilitätsforschung; Digitalisierung; Stadtplanung; Nachhaltige Verkehrsentwicklung